Intracellular NAD(+) depletion induces autophagic death in multiple myeloma cells - Cea, Michele (Landes Bioscience, 2013)
Multiple myeloma (MM) is a clonal B-cell malignancy characterized by the proliferation of plasma cells in the bone marrow. Despite recent therapeutic advances, MM remains an incurable disease. Therefore, research has focused on defining new aspects in MM biology that can be therapeutically targeted. Compelling evidence suggests that malignant cells have a higher nicotinamide adenine dinucleotide (NAD+) turnover rate than normal cells, suggesting that this biosynthetic pathway represents an attractive target for cancer treatment. We recently reported that an intracellular NAD(+)-depleting agent, FK866, exerts its anti-MM effect by triggering autophagic cell death via transcriptional-dependent (transcription factor EB, TFEB) and -independent (PI3K-MTORC1) mechanisms. Our findings link intracellular NAD(+) levels to autophagy in MM cells, providing the rationale for novel targeted therapies in MM.